2015
DOI: 10.3389/fendo.2015.00140
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Signal Activation by LH and hCG are Mediated by the LH/CG Receptor’s Extracellular Hinge Region

Abstract: The human lutropin (hLH)/choriogonadotropin (hCG) receptor (LHCGR) can be activated by binding two slightly different gonadotropic glycoprotein hormones, choriogonadotropin (CG) – secreted by the placenta, and lutropin (LH) – produced by the pituitary. They induce different signaling profiles at the LHCGR. This cannot be explained by binding to the receptor’s leucine-rich-repeat domain (LRRD), as this binding is similar for the two hormones. We therefore speculate that there are previously unknown differences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 44 publications
(80 reference statements)
0
33
0
Order By: Relevance
“…Previous studies have shown that deletion of LHR Exon10 impairs signaling of LH but not hCG (36,37). However, for those extracellular mutants with measurable signaling, there was a strong correlation between the potency measured for both ligands, suggesting that none of the mutants (including Del Exon 10) displayed bias for either hormone (Supplemental Figure 6).…”
Section: Del Exon 10 Mutants Are Retained But Have Enhanced Signalingmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that deletion of LHR Exon10 impairs signaling of LH but not hCG (36,37). However, for those extracellular mutants with measurable signaling, there was a strong correlation between the potency measured for both ligands, suggesting that none of the mutants (including Del Exon 10) displayed bias for either hormone (Supplemental Figure 6).…”
Section: Del Exon 10 Mutants Are Retained But Have Enhanced Signalingmentioning
confidence: 88%
“…Thus, retention is unlikely to be the sole cause of nonfunctionality. Indeed, previous studies have attributed nonfunctionality of Del Exon10 to an impaired responsiveness to LH, but not hCG (36,37), supported by the fact that LHRs of the New World monkey lineage, in which CG␤ has functionally replaced LH␤, do not contain Exon 10. Furthermore, a homozygous Del Exon10 patient seemed to have normal hCG-mediated fetal gonadal development, but lacked LH-mediated pubertal development.…”
Section: Class II Mutationsmentioning
confidence: 97%
“…In fact, there is a specific, distinct site of interaction located within this region of the human receptor [15, 56, 57]. We could speculate that the mouse-specific amino acid sequence at the hinge region is not able to qualitatively discriminate between LH and hCG, reflecting the evolutionary differences embedded into the primate-specific LH and hCG dual ligand system.…”
Section: Discussionmentioning
confidence: 99%
“…These gonadotropin-specific effects were amplified in the presence of FSH [16], suggesting that different activity at the receptor level and intracellular signaling activation characterize the two hormones [30]. Indeed, different binding affinity of LH and hCG for the rodent LH receptor was demonstrated three decades ago [31], providing the first evidence that these hormones interact with different binding sites of the common receptor.…”
Section: Discussionmentioning
confidence: 99%